Use of autogenous bone and beta-tricalcium phosphate in maxillary sinus lifting: a prospective, randomized, volumetric computed tomography study - Gorla, L. F. de O. [UNESP]; Spin-Neto, R.; Boos, F. B. D. J. [UNESP]; Pereira, R. dos S. [UNESP]; Garcia-Junior, I. R. [UNESP]; Vieira, Eduardo Hochuli [UNESP] (Elsevier B. V., 2015)
The correction of bone defects can be performed using autogenous or alloplastic materials, such as beta-tricalcium phosphate (β-TCP). This study compared the changes in bone volume (CBV) after maxillary sinus lifting using autogenous bone (n=12), autogenous bone associated with β-TCP 1:1 (ChronOS; DePuy Synthes, Paoli, CA, USA) (n=9), and β-TCP alone (n=11) as grafting material, by means of cone beam computed tomography (CBCT). CBV was evaluated by comparing CBCT scans obtained in the immediate postoperative period (5-7 days) and at 6 months postoperative in each group using OsiriX software (OsiriX Foundation, Geneva, Switzerland). The results showed an average resorption of 45.7±18.6% for the autogenous bone group, 43.8±18.4% for the autogenous bone+β-TCP group, and 38.3±16.6% for the β-TCP group. All bone substitute materials tested in this study presented satisfactory results for maxillary sinus lifting procedures regarding the maintenance of graft volume during the healing phase before the insertion of implants, as assessed by means of CBCT.
Keywords: Bone substitutes; Maxillary sinus; Maxillary sinus lifting